EVALUATION OF THE DIGITAL PRESENTATION OF THE FURNITURE AND EQUIPMENT IN CERTIFIED SPA AND WELLNESS CENTRES IN BULGARIA - D. Popova-Dobreava (Trakia Journal of Sciences)
PURPOSE The aim of the present study is to evaluate the digital internet information related to the available furniture and equipment in certified SPA and Wellness centers. METHODS An analysis of existing information related to the Dry and Wet High Temperature Section, as well as rooms for contrast procedures was made. The websites of the respective certified SPA and Wellness Centers were used for initial data. RESULTS The results obtained from our study demonstrate very good conditions and prerequisites for the development of the Spa and Wellness industry in our country. CONCLUSIONS The analysis of the summarized results reveals gaps in the digital presentation of the certified SPA and Wellness centers.